2009
DOI: 10.1002/j.2050-0416.2009.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenolic Acid on Antioxidant Activity of Wine and Inhibition of Pectin Methyl Esterase

Abstract: Antioxidant activity, malolactic fermentation and sensory evaluation of the grape must after fermentation in the presence of gallic acid and coumaric acid, as well as the inhibitory mechanism of gallic acid and coumaric acid on pectin methyl esterase (PME), were investigated. The content of malic acid and lactic acid increased 40.4% and 36.9% compared to the control when commercial pectic enzyme (CPE) was used. The increase in malic acid content was enhanced by 64.8% and 83.4%, compared to the control in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…As a result, high free-radical scavenging activities against the DPPH free radical were exhibited. These results are comparable to the results reported for the antioxidant activities in red grapes ( Vitis vinifera , L.) extracts [8, 9]. Moreover, we showed that enzymatic hydrolysates from honeybee-collected pollens possessed even higher antioxidative properties.…”
Section: Introductionsupporting
confidence: 91%
“…As a result, high free-radical scavenging activities against the DPPH free radical were exhibited. These results are comparable to the results reported for the antioxidant activities in red grapes ( Vitis vinifera , L.) extracts [8, 9]. Moreover, we showed that enzymatic hydrolysates from honeybee-collected pollens possessed even higher antioxidative properties.…”
Section: Introductionsupporting
confidence: 91%
“…Lewis et al (2008) found that green tea catechins can be used to inhibit PE activity across plant taxa and that the inhibitory interaction occurred at the substrate binding site of PE [10]. Chen et al (2009) showed that the addition of gallic acid and coumaric acid in the wine-making process may reduce methanol content by a mixed inhibition pattern of PE activity [22]. Previous studies indicated that phenolic compounds might have potential inhibitory activity toward PE.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27] The method used for ABTS •scavenging assay was reported by Re et al [28] All the results for the DPPH (ABTS) scavenging capacity of wine samples were expressed as trolox equivalent antioxidant capacity (TEAC). The standard solutions of trolox ranged from 0 to 400 mg/L.…”
Section: Dpph and Abts Free Radical Scavenging Capacitymentioning
confidence: 99%